Spin-Off Efficiency Analysis of Indonesian Islamic Banks - Sarifudin, Muhammad; Faturohman, Taufik (Journal of Business and Management, 2017)
Abstract - Since the Law No.21 of 2008 concerning Islamic Banking, there are only 4 Islamic business unit that have conducted spin-off which are BRI Sharia, BNI Sharia, Bukopin Sharia and BJB Sharia. The number of study regarding spin-off efficiency is still quite small. The study uses input-oriented VRS DEA model with intermediation approach to measure efficiency. Since the results show non-parametric data, Mann-Whitney test is used for hypothesis testing to examine the significant level of the efficiencies before and after conducting spin-off. The average efficiency of BRI Sharia, BNI Sharia, and BJB Sharia has improved after conducting spin-off. In the contrary, average efficiency of Bukopin Sharia has decreased after conducting spin-off. Looking at the trend-line, those four Islamic Banks possess better movement post spin-off than pre spin-off. There is no significant difference of BRI Sharia and BNI Sharia for both before and after conducting spin-off based on Mann-Whitney test. A significant difference occurs in Bukopin Sharia and BJB Sharia. Conventional commercial bank which has an Islamic business unit can learn about efficiency of pre and post-spin-off performances of 4 Islamic Commercial Banks that have performed spin-off to prepare adequate insight before actually conducting spin-off.Keywords: Data Envelopment Analysis, efficiency, intermediation approach, Islamic banks, spin-off